Prevalence of physical activity and sedentary-related behaviors among adolescents: data from the Qatar National School Survey. (July 2018) - Al-Thani, M.; Al-Thani, A.; Alyafei, S.; Al-Kuwari, M.G.; Al-Chetachi, W.; Khalifa, S.E.; Ibrahim, I.; Sayegh, S.; Vinodson, B.; Akram, H.
Abstract: Objectives: To investigate the prevalence of physical activity (PA) and sedentary behaviors among adolescents in Qatar by selected demographic characteristics. Study design: Cross-sectional study. Methods: A total of 5862 students (2938 boys and 2924 girls) in the age group 12–17 years were included in the analyses. PA and sedentary-related measures were obtained from the self-reported survey questions. Results: Only 35.4% of students were performing 60 min of PA ≥3 days/week. The proportion of students with >2 hr screentime ranged from 43% to 57% (weekdays) and 50% to 62.5% (weekends). Girls had less odds of being physically active than the boys (odds ratio [OR] = 0.61, P < 0.001). Qatari students were less likely to be physically active than non-Qataris (OR = 0.79, P < 0.001). Age was inversely correlated with PA ([r = −0.113, P < 0.001 for participation with sports team] and [r = −0.139, P < 0.001 for school physical education classes]). Participation in sports teams positively correlated with 60 min of PA number of days in a week (r = 0.317, P < 0.001). Conclusions: The study describes insufficient PA among youth as a public health issue of concern in the State of Qatar that requires multipronged health promotion initiatives. Highlights: Overall, the screen time among sample is high both during weekdays and weekends. The extent of physical activity (PA) and sedentary behavior differs by sex, nationality, and age. Multi-dementional methods are required to promote physical activity and reducing screen time among youth in Qatar.